Consumption and savings of migrants in China – social cohesion perspective. Issue 1 (31st December 2022) - Tan, Jing; Xu, Hao; Yu, Jingwen; Radu, Valentin
Abstract: Boosting domestic demand is the task of China's sustainable economic development, and in particular, China has become an important global consumer market and the savings patterns should be more cohesive and without discriminations. Using data of China Migrants Dynamic Survey, the paper provides new evidence on internal migrants' savings in China from the perspective of homeownership and family migration. We find that migrants' savings are 5.25–6.60 percentage points higher than hukou population even when controlling for working, social status, and social insurance coverage which means the migrant will save 1019.88–1647.10 yuan in 2010 price more monthly. Furthermore, we discover housing could partly explain the saving gap, while when we take remittance and family migration into account, the saving rate differences between migrants and hukou population disappears, which means migrants may save to consume when they go back to their hometown with their family members instead of consuming later in the resident cities. The research is carried out taking into account the objectives of social cohesion policy identified at national and international level and their involvement in consumption and saving processes. Our empirical results reveal that homeownership, remittance motive and family migration play important roles in shaping saving behaviour of migrants.